2015
DOI: 10.1039/c5ce00999e
|View full text |Cite
|
Sign up to set email alerts
|

Mesoxalate as Cu(ii)–Ln(iii) linker in the construction of MOFs in DMSO/water medium

Abstract: Fivenew heterometallic 3d-4f metal-organic frameworks with the general formula ijLnIJH 2 O) z Cu 3 IJHmesox) 3 DMSO]·xH 2 O·yDMSO IJLnIJIII) = La, Ce, Pr, Nd and Eu; H 4 mesox = mesoxalic or dihydroxymalonic acid; and DMSO = dimethylsulfoxide) have been prepared by crystal growth in agarose gel in a mixed solvent (DMSO/water) medium. LaCu 3 , CeCu 3 , PrCu 3 and NdCu 3 yield prismatic wellformed chiral crystals, whereas EuCu 3 produces laminar and badly-shaped crystals. The structural analysis shows cubic neutral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 53 publications
(119 reference statements)
0
16
0
Order By: Relevance
“…[Ln(H 2 O) z Cu 3 (Hmesox) 3 DMSO] ⋅ xH 2 O ⋅ yDMSO materials (Ln(III)=La, Ce, Pr, Nd and Eu; H 4 mesox=dihydroxymalonic acid; and DMSO=dimethylsulfoxide) have been prepared by crystal growth in agarose gel in a mixed solvent (DMSO/water) medium. The magnetic susceptibility study performed for LaCu 3 revealed the occurrence of antiferromagnetically coupled Cu(II) equilateral triangles whose apical positions can also be occupied by water molecules . Tripuramallu et al .…”
Section: Mofs With Linkers Containing Metal‐binding Sitesmentioning
confidence: 99%
“…[Ln(H 2 O) z Cu 3 (Hmesox) 3 DMSO] ⋅ xH 2 O ⋅ yDMSO materials (Ln(III)=La, Ce, Pr, Nd and Eu; H 4 mesox=dihydroxymalonic acid; and DMSO=dimethylsulfoxide) have been prepared by crystal growth in agarose gel in a mixed solvent (DMSO/water) medium. The magnetic susceptibility study performed for LaCu 3 revealed the occurrence of antiferromagnetically coupled Cu(II) equilateral triangles whose apical positions can also be occupied by water molecules . Tripuramallu et al .…”
Section: Mofs With Linkers Containing Metal‐binding Sitesmentioning
confidence: 99%
“…In the last decade, we have studied the formation of coordination polymers with the mesoxalate ligand, the conjugated base of the mesoxalic acid (mesoxalic acid=2,2‐dihydroxyl‐propanedioic acid or 2,2‐dihydroxyl‐malonic acid, H 4 mesox) (Scheme 1). This ligand has six‐donor oxygens, four from the two carboxylate groups and two from the two hydroxyl groups, and it's complex formation has resulted in great structural diversity [1–10] …”
Section: Introductionmentioning
confidence: 99%
“…This ligand has six-donor oxygens, four from the two carboxylate groups and two from the two hydroxyl groups, and it's complex formation has resulted in great structural diversity. [1][2][3][4][5][6][7][8][9][10] In some of the complexes we have prepared such as (Ph 4 P)[MnCu 3 (Hmesox) 3 Cl] or [LaCu 3 (Hmesox) 3 (DMSO)], the mesoxalate ligand acted as Hmesox 3À giving the [Cu 3 (Hmesox) 3 X] 4À (X=Cl À and Br À ) and [Cu 3 (Hmesox) 3 Y] 3À (Y=H 2 O or DMSO) trinuclear copper(II) metalloligands. [5][6][7]9,10] Furthermore, it acted as H 2 mesox 2À when linked to Ln(III) in [Ln 2 (H 2 mesox) 6 ] • 6H 2 O compounds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations